2020
DOI: 10.3390/sports8100134
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory and Lower-Limb Strength Importance in Mountain Ultramarathon Running. Sex Differences and Relationship with Performance

Abstract: The study was aimed at comparing lower-limb strength and respiratory parameters between male and female athletes and their interaction with performance in a 107 km mountain ultramarathon. Forty seven runners (29 males and 18 females; mean ± SD age: 41 ± 5 years) were enrolled. Lower-limb strength assessment comprised a squat jump test, an ankle rebound test, and an isometric strength test. Respiratory assessment included pulmonary function testing and the measurement of maximal inspiratory pressure. Male athle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
(62 reference statements)
1
5
0
Order By: Relevance
“…Accordingly, the negative correlation of the number of finished marathons with SJ and CMJ might reflect a training adaptation to endurance training. This finding was in agreement with previous research (Martinez-Navarro et al, 2020) that observed a trend that fast runners exhibited relatively low SJ, too. With regard to the variation of skinfold thickness and body fat between the two groups, EXP had smaller thickness in two skinfolds (abdominal and iliac crest) and lower BF estimated by BIA than NOV.…”
Section: Discussionsupporting
confidence: 94%
“…Accordingly, the negative correlation of the number of finished marathons with SJ and CMJ might reflect a training adaptation to endurance training. This finding was in agreement with previous research (Martinez-Navarro et al, 2020) that observed a trend that fast runners exhibited relatively low SJ, too. With regard to the variation of skinfold thickness and body fat between the two groups, EXP had smaller thickness in two skinfolds (abdominal and iliac crest) and lower BF estimated by BIA than NOV.…”
Section: Discussionsupporting
confidence: 94%
“…Five of the six studies found sex differences in the predictors of performance. Martinez-Navarro et al found that mean inspiratory pressure was correlated with performance in males only ( r = − 0.576, p = 0.010) [ 28 ]. In females, the Leg Qindex was the only variable that correlated with performance ( r = − 0.607, p = 0.028) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Martinez-Navarro et al found that mean inspiratory pressure was correlated with performance in males only ( r = − 0.576, p = 0.010) [ 28 ]. In females, the Leg Qindex was the only variable that correlated with performance ( r = − 0.607, p = 0.028) [ 28 ]. In another paper, Martinez-Navarro et al reported that Vpeak, or the top speed measured during treadmill cardiopulmonary exercise testing (CPET), and maximal fat oxidation rate (MFO) together explained 66% of the variation in 107 km race time in males [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations